An optimization study on surface grinding stainless steel - Dung Hoang, Tien; Hong Tran, Thi; Van Cuong, Nguyen; Ky Le, Hong; Thi Thanh Nga, Nguyen; Tu Nguyen, Thanh; Hung Le, Xuan; Tung Luu, Anh (International Journal of Engineering and Technology, 2019)
This paper presents a study on optimization of the exchanged grinding wheel diameter based on the analysis cost for surface grind-ing stainless steel. The optimum exchanged grinding wheel diameter is determined by minimizing the cost function. An experi-mental design was conducted to describe the influence of the input technological parameters i.e., the initial grinding wheel diameter, the grinding wheel width, the total depth of dressing cut, the Rockwell hardness of workpiece, the wheel life, and the radial grind-ing wheel wear per dress and the cost components i.e., the machine tool hourly rate and the grinding wheel cost on the optimum diameter. Based on the regression analysis, a mathematical model to compute the optimum diameter was resulted as an explicit equation. The reliability of the mathematical model is verified by the result of the experiment. The difference of optimum diameter between the model and the experiment was 1.7%. For these results, the proposed model can be used for calculating the optimum exchanged grinding wheel for surface grinding; therefore, this can increase the economic and technical effectiveness of the grinding process.Â Â
Keywords: Grinding; Surface Grinding; Cost Optimization; the Exchanged Grinding Wheel Diameter.